-4n+7-3n-2=

Simple and best practice solution for -4n+7-3n-2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4n+7-3n-2= equation:


Simplifying
-4n + 7 + -3n + -2 = 0

Reorder the terms:
7 + -2 + -4n + -3n = 0

Combine like terms: 7 + -2 = 5
5 + -4n + -3n = 0

Combine like terms: -4n + -3n = -7n
5 + -7n = 0

Solving
5 + -7n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + -7n = 0 + -5

Combine like terms: 5 + -5 = 0
0 + -7n = 0 + -5
-7n = 0 + -5

Combine like terms: 0 + -5 = -5
-7n = -5

Divide each side by '-7'.
n = 0.7142857143

Simplifying
n = 0.7142857143

See similar equations:

| 4x-12.52=3x+12.48 | | -10x+122=282 | | 10=-4m-6m | | 0.6x-2=0.28x+6 | | 23-5-5= | | (3x-5)(x+3)=(3x-5)(-3x-1) | | -9x-45=171 | | 0.4x-4=0.05x+3 | | -47-5x=-137 | | 1=5n-3-1 | | 0.3x-1=0.5x+4 | | 2y-5n= | | 24+8x=-96 | | -4K+3=-13 | | 10x+61=-59 | | 5.25+b=22.75 | | 8x+16=100 | | 40-6x=-116 | | g(x)=1482 | | 0.5x*10=0.15 | | 14n^2/2n^2 | | -5(x-6)=-34+3x | | 3m-m^2=2 | | -18x+102=354 | | 0.6-4=2.6 | | 10=0.10x | | 9x+27=100 | | 10/0.10 | | 8+8m=4+8m+8 | | 8+8m=4+8m+4 | | 3x-2+4=70 | | 5n-n=15+7 |

Equations solver categories